Dietary Antioxidants and their Potential Role in Human Disease Management - Saini, Rashmi; Mehra, Himaani; Goyal, Tanisha; Dhiman, Neena K. (Current Nutrition & Food Science, 2023)
Reactive oxygen species (ROS) are usually destroyed by the antioxidant defence systems in our body. ROS in low concentrations may be beneficial or even indispensable for defence against microorganisms and in intracellular signaling, but its higher amounts can trigger negative chain reactions leading to various pathological conditions. A delicate balance between antioxidants and oxidants is maintained in healthy organisms and protection against the harmful effects of ROS is thus provided. The increase in ROS leading to oxidative stress plays a key role in the development of chronic diseases like cancer, diabetes, neurodegenerative, and cardiovascular diseases. Several non-enzymatic and enzymatic antioxidant activities exist as a safeguard against ROS accumulation. Imbalance between the oxidative stress and the antioxidant defence systems causes irreversible changes in cellular components and the normal cell signaling mechanisms are disrupted. The enzymatic and non-enzymatic antioxidant defences include catalase (CAT), superoxide dismutase (SOD), glutathione (GSH), glutathione peroxidase (GPx), vitamin A, vitamin C (ascorbic acid), vitamin E (α-tocopherol), carotenes, flavonoids, etc. Several human pathologies have been known to be treated by the use of medicinal plants owing to their antioxidant properties. Dietary antioxidants such as vitamins, minerals, carotenes, and flavonoids, with their mechanisms of antioxidant defence are discussed in the review for the effective management of various human diseases.
Keywords: Free radicals